KONFLIK INDONESIA-JEPANG DI DALAM PASAR OTOMOTIF: PENERAPAN ANALYTIC HIERARCHY PROCESS (AHP) DAN GAME THEORY - Ahmad Jamli; Jose Rizal Joesoef (Journal of Indonesian Economy and Business (JIEB), 1999)
This study stipulates the conflict between Indonesia and Japan due to seriousallegations of the National Car program that is seemingly to protect Indonesiandomestic automotive market. Being aware of potential new conflicts and assuming theprogram is still upheld, the nature and intensity of the conflict are describedquantitatively by applying the Analytic Hierarchy Process (AHP) in a non-zero sumgame framework. The AHP is used to find relative importance of strategies that arepossible to be implemented by Indonesia and Japan and to measure their payoffs.